Does Gender Matter for Economic Convergence? The OECD Evidence - Dilara Kýlýnç; Hakan Yetkiner (Izmir University of Economics, Department of Economics, 2013)
This work studies the role of gender on economic convergence in a standard convergence model expanded by gender shares of labor force. The theoretical part of the paper shows the positive role of gender on economic growth. Next, the paper presents 5-year span panel data tests of the contribution of the female share in employment on economic growth for 34 OECD countries in the period 1951-2010. We find that an increase in the share of women has a positive contribution to economic convergence across OECD countries. In addition to this, we also show that there is a U-shaped curvilinear relationship between gender equality and economic growth for OECD countries in the period 1951-2010. We conjecture that this result coincides with the 'S-shaped' Kuznets Curve of Gender hypothesis.
Keywords: J16; O47; O50; C23; F23; 330; Gender; Income Convergence; Economic Growth; Kuznets Curve of Gender; Geschlechterdiskriminierung; Wirkungsanalyse; Wirtschaftswachstum; Kuznets-Kurve; EU-Mitgliedschaft; Türkei; OECD-Staaten